Abnormal vaginal colonization by gram-negative bacteria is significantly higher in pregnancy conceived through infertility treatment compared to natural pregnancy. (4th March 2017) - Kim, Ji Y.; Sung, Ji-Hee; Chang, Kylie Hae-Jin; Choi, Suk-Joo; Oh, Soo-young; Roh, Cheong-Rae; Kim, Jong-Hwa
Abstract: Objective : To compare abnormal vaginal colonization between natural pregnancy and pregnancy by infertility treatment in high-risk parturient women and to examine the association between abnormal vaginal colonization and early-onset neonatal sepsis (EONS). Methods : The clinical characteristics, vaginal culture result, and delivery outcome of patients who admitted to our high-risk unit between 2005 and 2014 were retrospectively reviewed and compared. We investigated the prevalence of EONS according to maternal vaginal colonization and examined the concordance between maternal vaginal bacteria and etiologic microorganism causing EONS. Results : Among 1096 pregnancies, the rate of vaginal colonization by gram-negative bacteria, especially Escherichia coli was significantly higher in pregnancies by infertility treatment after adjustment of confounding variables ( E. coli, OR [95% CI]: 2.47 [1.33–4.57], p  = 0.004). The rate of EONS was significantly higher in neonates with maternal abnormal vaginal bacteria colonization (OR [95% CI]: 3.38 [1.44–7.93], p  = 0.005) after adjusting for confounding variables. Notably, among microorganisms isolated from maternal vagina, E. coli and Staphylococcus aureus were consistent with the results from neonatal blood culture in EONS. Conclusions : Our data implicate a possible association between gram-negative bacteria colonization and infertility treatment and suggest that maternal vaginal colonization may be associated with EONS of neonates in high-risk pregnancy.